Transportation Route Shifts Impacts on The Deterioration of Facades in Kalimas Timur - Agustianti, Stefani Widya; Dharmatanna, Stephanus Wirawan (Journal of Artificial Intelligence in Architecture, 2025)
Historically, Indonesia's strategic location on international trade routes facilitated the development and growth of port cities throughout Indonesia. Historically, rivers were the city's main transportation route, leading to urban settlements along the river banks. Surabaya is one of the cities in Indonesia that relies on waterways as its main transportation route. However, population growth accompanied by the expansion of road transportation modes gradually reduced the role of the river as the main route. The shift has resulted in areas around the river becoming undeveloped and unmaintained. This research uses a space syntax approach to study the impact of the transportation shift in Surabaya from waterway to landline on the condition of facades along Jalan Kalimas Timur. The quantitative method descriptively uses data collected through literature study and field observation. The data obtained was then analysed using DepthMapX software. The results of this study show that the shift in transportation routes impacts the maintenance of facades along Kalimas Timur Street, which tends to be less maintained, making the area that was once the centre of the city now a neglected and damaged area.